The definition of family medicine in sub-Saharan Africa - Bob Mash (South African Family Practice)
At a recent presentation of the study Exploring the key principles of Family Medicine in Sub-Saharan Africa1 one of the audience challenged me by saying “So, where is the definition?” This editorial is an attempt to answer this question in the spirit of eliciting further dialogue and debate.